Cellulose acetate and method for producing cellulose acetate
By solvate the raw material cellulose acetate deacetylation, and using specific solvents and catalysts, cellulose acetate with low total acetyl substitution degree and 6-position acetyl substitution degree are prepared, which solves the problem of insufficient biodecomposition and water solubility in the prior art, and achieves efficient biodecomposition and excellent physiological effects.
Patent Information
- Application Number
- CN202411963495.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2019-07-01
- Filing Date
- 2020-06-24
- Publication Date
- 2025-04-08
AI Technical Summary
It is difficult to prepare cellulose acetate with low total acetyl substitution degree, especially low acetyl substitution degree and excellent water solubility in the prior art, which affects its biodecomposition and physiological effects.
The solvent-free acetylation step is performed on the raw material cellulose acetate having a total acetyl substitution degree of 1.5 to 3.0, and deacetylation is performed at a temperature above the boiling point of the alcohol by using a solvent containing an alcohol having a carbon atom of 3 or less, and an acid catalyst, to produce cellulose acetate having a low acetyl substitution degree of 6 positions.
The preparation of cellulose acetate with low total acetyl substitution degree, relatively reduced acetyl substitution degree at 6 position and excellent water solubility was achieved, which improved its biodecomposition and physiological effects.
Smart Images

Figure BDA0005217768190000231 
Figure BDA0005217768190000261
Abstract
Description
[0001] This application is a divisional application of an invention patent application with an application date of June 24, 2020, application number 202080013954.X (PCT / JP2020 / 024720), and invention name “Cellulose acetate and method for producing cellulose acetate”. Technical Field
[0002] The present invention relates to cellulose acetate and a method for producing cellulose acetate. Background Art
[0003] It is known that low-substituted cellulose acetate having a total acetyl substitution degree of 0.4 to 1.1 and water-soluble cellulose acetate having a total acetyl substitution degree of about 0.8 (low-substituted cellulose acetate) are metabolized and decomposed by intestinal bacteria and exhibit physiological effects such as suppressing weight gain and lowering blood cholesterol (Patent Document 1 and Non-Patent Document 1).
[0004] The main metabolic degradation products of low-substituted cellulose acetate are acetic acid and propionic acid. Propionic acid is believed to be produced from glucose constituting cellulose via phosphoenolpyruvic acid and succinic acid (Non-Patent Documents 2 and 3). Acetic acid is believed to be produced by the release of acetic acid bound to cellulose in low-substituted cellulose acetate, and is also believed to be produced from glucose constituting cellulose via phosphoenolpyruvic acid (Non-Patent Documents 2 and 3).
[0005] As for acetic acid and propionic acid produced by the metabolic decomposition of low-substituted cellulose acetate by intestinal bacteria, it is known that on the one hand, they act on the nuclear receptor GPR43 of intestinal L cells to produce incretin GLP-1, thereby affecting appetite and sugar metabolism (Non-patent Document 4), and on the other hand, they act on the hypothalamus to affect appetite suppression, weight gain suppression, sugar metabolism, and lipid metabolism (Non-patent Document 5).
[0006] It is known that acetylxylan esterase, an enzyme, is involved in the deacetylation of low-substituted cellulose acetate (Non-patent Document 6). It should be noted that Bacteroides xylanisolvens (Patent Document 1, Non-patent Document 1), which provides low-substituted cellulose acetate and proliferates in the intestine of rats, has been well studied as a xylan decomposing bacterium and is believed to have acetylxylan esterase. It can be inferred that in the metabolic decomposition of low-substituted cellulose acetate by intestinal bacteria, the initial decomposition is deacetylation, and acetylxylan esterase is believed to be involved in this decomposition.
[0007] There are hydroxyl groups at the 2-, 3-, and 6-positions of glucose contained as the main structural unit of cellulose. In low-substituted cellulose acetate, some of these hydroxyl groups are acetylated. In addition, acetylxylan esterase selectively removes the acetyl group at the 2- or 3-position, but hardly removes the acetyl group at the 6-position (Non-Patent Document 6).
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent No. 6453851
[0011] Non-patent literature
[0012] Non-patent document 1: Genda et al., Journal of Agricultural and Food Chemistry, 66, 11909-11916 (2018).
[0013] Non-patent document 2: Gijs den Besten et al., Journal of Lipid Research, 54, 2325-2340 (2013).
[0014] Non-patent document 3: Strobel, Applied and Environmental Microbiology, 58, 2331-2333 (1992).
[0015] Non-patent document 4: Sleeth et al., Nutrition Research Reviews, 23, 135-145 (2010).
[0016] Non-patent document 5: Frost et al., Nature Communications, DOI: 10.1038 (2014).
[0017] Non-patent document 6: Puls et al., Mactomolecular Symposia, 208, 239-253 (2004).
[0018] Non-patent document 7: Buchanan et al., Macromolecules, 24, 3060-3064 (1991). Summary of the invention
[0019] Problems to be solved by the invention
[0020] Low-substituted cellulose acetate is considered to exhibit physiological effects through metabolic degradation by intestinal bacteria. Low-substituted cellulose acetate, which is biodegradable and easily metabolically degraded by intestinal bacteria, is expected to exhibit excellent physiological effects.
[0021] Since acetylxylan esterase hardly removes the acetyl group at the 6th position, in order to improve the biodegradability of low-substituted cellulose acetate, the degree of acetyl substitution at the 6th position needs to be relatively reduced relative to the degree of acetyl substitution at the 2nd and 3rd positions of the glucose ring of cellulose acetate.
[0022] However, conventional methods cannot reduce the degree of acetyl substitution at the 6th position of the glucose ring relative to the degrees of acetyl substitution at the 2nd and 3rd positions in cellulose acetate having a low total degree of acetyl substitution.
[0023] The more excellent the water solubility of low-substituted cellulose acetate is, the higher its biodegradability is. Therefore, low-substituted cellulose acetate having a low degree of substitution of acetyl groups at the 6-position and excellent water solubility is particularly excellent in biodegradability.
[0024] However, such low-substituted cellulose acetate having a low degree of substitution of acetyl groups at the 6th position and excellent water solubility is not known. For example, the degree of substitution of acetyl groups at the 6th position in the low-substituted cellulose acetate disclosed in Patent Document 1 is not low. Although low-substituted cellulose acetate having a low degree of substitution of acetyl groups at the 6th position is disclosed as Experiment Nos. 6 and 7 in Non-Patent Document 7, the water solubility is insufficient.
[0025] An object of the present invention is to provide cellulose acetate having a low total degree of acetyl substitution, a low degree of acetyl substitution at the 6th position relative to the degree of acetyl substitution at the 2nd and 3rd positions of the glucose ring, and excellent water solubility.
[0026] Means for solving problems
[0027] A first aspect of the present disclosure relates to cellulose acetate having a total degree of acetyl substitution of 0.4 to 0.9, a proportion of the degree of acetyl substitution at position 6 in the total degree of acetyl substitution of 0% to 18%, and a light transmittance at 660 nm of a 4 wt % aqueous solution of 5% or more.
[0028] In the cellulose acetate, the light transmittance of the 4 wt % aqueous solution at 660 nm may be 80% or more.
[0029] A second aspect of the present disclosure relates to a method for producing the above-mentioned cellulose acetate, comprising the following steps: a step of deacetylating a raw material cellulose acetate having a total degree of substitution of acetyl groups of 1.5 to 3.0 by solvolysis; and a step of precipitating cellulose acetate produced by deacetylation of the raw material cellulose acetate, wherein the solvolysis of the raw material cellulose acetate is performed in the presence of a solvent containing an alcohol having 3 or less carbon atoms and an acid catalyst at a temperature not lower than the boiling point of the alcohol.
[0030] In the method for producing cellulose acetate, the acid catalyst may have an acid dissociation constant pKa of 0 or less in water at 25°C.
[0031] In the method for producing cellulose acetate, the acid catalyst may be sulfuric acid.
[0032] In the method for producing cellulose acetate, the alcohol may be methanol.
[0033] In the method for producing cellulose acetate, the solvent may contain acetate.
[0034] The method for producing cellulose acetate may include the steps of: dissolving the precipitated cellulose acetate in water to remove residues; and precipitating the dissolved cellulose acetate.
[0035] The method for producing cellulose acetate may include the steps of: dissolving the precipitated cellulose acetate in water and centrifugally separating the precipitated cellulose acetate to remove residues; and reprecipitating the dissolved cellulose acetate.
[0036] Effects of the Invention
[0037] According to the present invention, cellulose acetate having a low total acetyl substitution degree, a low acetyl substitution degree at the 6th position relative to the acetyl substitution degrees at the 2nd and 3rd positions of the glucose ring, and excellent water solubility can be provided. DETAILED DESCRIPTION
[0038] [Cellulose acetate]
[0039] The cellulose acetate of the present disclosure has a total degree of acetyl substitution of 0.4 to 0.9, a proportion of the degree of acetyl substitution at position 6 in the total degree of acetyl substitution of 0% to 18%, and a light transmittance of 4 wt % aqueous solution at 660 nm of 5% or more.
[0040] [Total degree of acetyl substitution]
[0041] The total degree of acetyl substitution of the cellulose acetate of the present disclosure is 0.4 or more and 0.9 or less. When the total degree of acetyl substitution is within this range, the cellulose acetate of the present disclosure has excellent water solubility and biodegradability. It should be noted that the total degree of acetyl substitution of the cellulose acetate of the present disclosure is 0.4 or more and 0.9 or less, and it is sometimes referred to as low-substituted cellulose acetate.
[0042] [Ratio of acetyl substitution degree at position 6]
[0043] In the cellulose acetate of the present disclosure, the ratio of the acetyl substitution degree at the 6-position to the total acetyl substitution degree is 0% to 18%, and the ratio of the acetyl substitution degree at the 6-position is preferably 17% or less, more preferably 14% or less, and further preferably 10% or less. The ratio of the acetyl substitution degree at the 6-position is most preferably 0%, but may exceed 0%, may be 4% or more, may be 7% or more, and may be 9% or more. By making it 18% or less, the decomposition property by enzymes (e.g., acetyl xylan esterase, etc.) present in the intestine is excellent, and it is easily metabolized in the body.
[0044] The total degree of acetyl substitution and the ratio of the degree of acetyl substitution at the 6-position to the total degree of acetyl substitution can be determined by the following method.
[0045] First, the degree of acetyl substitution at the 2nd, 3rd, and 6th positions of the glucose ring of cellulose acetate was measured by NMR according to the method of Tezuka (Carbonydr. Res. 273, 83 (1995)). That is, the free hydroxyl groups of cellulose acetate were propionylated with propionic anhydride in pyridine. The obtained sample was dissolved in deuterated chloroform and measured. 13 C-NMR spectrum. The carbon signals of the acetyl group appear in the order of position 2, position 3, and position 6 from the high magnetic field in the region of 169ppm to 171ppm, and the carbonyl carbon signals of the propionyl group appear in the same order in the region of 172ppm to 174ppm. The degree of substitution of acetyl groups at positions 2, 3, and 6 of the glucose ring of cellulose acetate can be determined based on the abundance ratio of acetyl groups to propionyl groups at each corresponding position. In addition, 13 In addition to C-NMR, 1 H-NMR was used to analyze the degree of acetyl substitution.
[0046] The degree of acetyl substitution at position i is a value obtained by dividing the number of moles of acetyl groups at position i by the sum of the number of moles of acetyl groups at position i and the number of moles of hydroxyl groups, and is a real number between 0 and 1. Here, i is any one of 2, 3, and 6. In addition, the sum of the degrees of acetyl substitution at positions 2, 3, and 6 of the glucose ring of cellulose acetate is the total degree of acetyl substitution. In addition, the ratio of the degree of acetyl substitution at position 6 to the sum of the degrees of acetyl substitution at positions 2, 3, and 6 of the glucose ring of cellulose acetate is the ratio (%) of the degree of acetyl substitution at position 6 to the total degree of acetyl substitution.
[0047] In addition, the total degree of acetyl substitution can be converted into the degree of acetylation using the following formula.
[0048] DS=162.14×AV×0.01 / (60.052-42.037×AV×0.01)
[0049] DS: total degree of acetyl substitution
[0050] AV: Acetylation degree (%)
[0051] [Light transmittance]
[0052] The cellulose acetate of the present disclosure has a light transmittance of 5% or more at 660 nm of a 4 wt% aqueous solution of the cellulose acetate, preferably 10% or more, more preferably 30% or more, further preferably 50% or more, and most preferably 80% or more. The light transmittance may be 99% or less, 98% or less, or 95% or less. When the light transmittance of a 4 wt% aqueous solution at 660 nm is less than 5%, the water solubility of the cellulose acetate is poor.
[0053] The transmittance of a 4 wt % aqueous solution of cellulose acetate at 660 nm can be determined using a spectrophotometer (manufactured by Shimadzu Corporation, UV-1800 ultraviolet-visible spectrophotometer, cell material: polystyrene, cell length: 10 mm).
[0054] [Degree of Polymerization (viscosity average degree of polymerization)]
[0055] The viscosity average polymerization degree of the cellulose acetate of the present disclosure is not particularly limited, but is preferably 3 to 400, more preferably 10 to 200, and further preferably 15 to 150. When the viscosity average polymerization degree is within this range, the cellulose acetate has particularly excellent water solubility and biodegradability.
[0056] As shown below, the viscosity average degree of polymerization (DP) can be evaluated as a viscosity average degree of polymerization based on the intrinsic viscosity number ([η], unit: g / ml). Specifically, the intrinsic viscosity number can be obtained by a method in accordance with JIS-K-7367-1 and ISO1628-1, the viscosity average molecular weight can be calculated according to the literature of Kamide et al., and the viscosity average degree of polymerization can be calculated based on the viscosity average molecular weight.
[0057] The cellulose acetate of the present disclosure can be produced by the following production method.
[0058] The cellulose acetate of the present disclosure has a low total degree of acetyl substitution and a low degree of acetyl substitution at the 6th position relative to the degrees of acetyl substitution at the 2nd and 3rd positions of the glucose ring. Therefore, it is excellent in decomposability by enzymes present in the intestine (e.g., acetylxylan esterase, etc.), is easily metabolized in the body, and can be used as a food.
[0059] [Method for producing cellulose acetate]
[0060] The method for producing cellulose acetate of the present disclosure comprises the following steps: a step of deacetylating raw material cellulose acetate having a total degree of substitution of acetyl groups of 1.5 to 3.0 by solvolysis; and a step of precipitating cellulose acetate produced by deacetylation of the raw material cellulose acetate, wherein the solvolysis of the raw material cellulose acetate is carried out in the presence of a solvent containing an alcohol having 3 or less carbon atoms and an acid catalyst at a temperature not lower than the boiling point of the alcohol.
[0061] [Deacetylation process]
[0062] In the deacetylation step in the method for producing cellulose acetate of the present disclosure, cellulose acetate as a raw material is subjected to solvolysis. In the deacetylation step of the present disclosure, deacetylation is performed by solvolysis. The solvolysis includes the following cases: a case where only a solvent containing an alcohol having 3 or less carbon atoms participates; and a case where a solvent containing an alcohol having 3 or less carbon atoms and other solvents such as water participate. Solvolysis also includes hydrolysis.
[0063] (Raw material: Cellulose acetate)
[0064] As the raw material cellulose acetate, cellulose acetate with a medium to high degree of substitution can be used. The cellulose acetate with a medium to high degree of substitution used as the raw material has a total degree of substitution of acetyl groups of 1.5 to 3.0, preferably 1.5 to 2.5. As the raw material cellulose acetate, commercially available cellulose diacetate (total degree of substitution of acetyl groups of 2.20 to 2.56) and cellulose triacetate (total degree of substitution of acetyl groups of more than 2.56 and 3 or less) can be used.
[0065] When manufacturing the raw material cellulose acetate, it can be manufactured by a conventionally known manufacturing method. For example, it can be manufactured through a series of steps including: a step of pulverizing pulp as a cellulose material; a step of performing a pretreatment; a step of performing an acetylation; a step of performing a hydrolysis; a step of performing a precipitation; and a step of adding a stabilizer. Next, each of the above steps will be described. It should be noted that for the conventional manufacturing method of cellulose acetate, reference can be made to "Wood Chemistry" (Volume 1) (Uda et al., Kyoritsu Publishing Co., Ltd., published in 1968, pages 180 to 190).
[0066] The α-cellulose content of the pulp is preferably 92% by weight or more, more preferably 93% by weight or more, and even more preferably 94% by weight or more. The upper limit is not particularly limited, and may be 99% by weight or less. Such high-purity pulp contains almost no lignin derived from wood, and also contains little hemicellulose. The reason for reducing these impurities is that cellulose acetate, which is particularly excellent in water solubility and biodegradability, can be obtained.
[0067] The α-cellulose content can be determined as follows. Pulp of known weight is continuously extracted with 17.5% and 9.45% aqueous sodium hydroxide solutions at 25°C, and the soluble portion of the extract is oxidized with potassium dichromate. The weight of β-cellulose and γ-cellulose is determined based on the volume of potassium dichromate required for oxidation. The value obtained by subtracting the weight of β-cellulose and γ-cellulose from the initial pulp weight is taken as the weight of the insoluble portion of the pulp, i.e., the weight of α-cellulose (TAPPI T203). The ratio of the weight of the insoluble portion of the pulp to the initial pulp weight is the α-cellulose content (weight %).
[0068] As pulp, wood pulp (conifer pulp, broadleaf pulp) and cotton linters can be used. These celluloses can be used alone or in combination of two or more. For example, conifer pulp can be used in combination with cotton linters or broadleaf pulp.
[0069] Wood pulp is preferred because it has a stable supply of raw materials and is cost-effective compared to linters. Examples of wood pulp include hardwood pre-hydrolyzed kraft pulp and the like.
[0070] In the step of pulverizing the pulp, for example, the pulp can be pulverized in a dry manner using a disk refiner.
[0071] In the pretreatment step, the pulverized pulp is contacted with acetic acid or sulfur-containing acetic acid. Acetic acid can be used in an amount of 96 to 100% by weight, and sulfur-containing acetic acid is acetic acid containing sulfuric acid, preferably containing 1 to 10% by weight of sulfuric acid.
[0072] In the acetylation step, the pretreated pulp is brought into contact with a mixed solution of acetic acid and acetic anhydride, and the pulp is acetylated by acetic anhydride to obtain completely tri-substituted cellulose acetate (primary cellulose acetate). The mixed solution preferably contains sulfuric acid as a catalyst. In the acetylation step, 96 to 100% by weight of acetic acid can be used, and concentrated sulfuric acid is preferably used.
[0073] In the hydrolysis step, a neutralizing agent such as water, dilute acetic acid, or an aqueous solution of magnesium acetate is added to neutralize (completely or partially neutralize) the sulfuric acid and inactivate the acetic anhydride, thereby terminating the acetylation reaction. In this way, completely tri-substituted cellulose acetate (primary cellulose acetate) is hydrolyzed to obtain cellulose acetate (secondary cellulose acetate) of a desired degree of substitution. Here, dilute acetic acid refers to an aqueous solution of acetic acid at 1 to 50% by weight. In addition, the magnesium acetate concentration of the aqueous solution of magnesium acetate is preferably 5 to 30% by weight.
[0074] In the precipitation step, a mixture containing cellulose acetate is mixed with a precipitant such as water, dilute acetic acid, dilute potassium hydroxide aqueous solution, or magnesium acetate aqueous solution to precipitate cellulose acetate. The generated cellulose acetate (precipitate) is then separated and washed with water to remove free metal components, sulfuric acid components, and the like.
[0075] In the step of adding a stabilizer, in addition to water washing, an alkali metal compound and / or an alkaline earth metal compound (especially a potassium compound such as potassium hydroxide) may be added as a stabilizer as needed.
[0076] (Solvolysis of raw material cellulose acetate)
[0077] The solvolysis of the raw material cellulose acetate is carried out in the presence of a solvent containing an alcohol having 3 or less carbon atoms and an acid catalyst at a temperature not less than the boiling point of the alcohol.
[0078] The solvent containing an alcohol having 3 or less carbon atoms may be any solvent as long as it contains an alcohol having 3 or less carbon atoms and can dissolve the raw material cellulose acetate. The term "capable of dissolving the raw material cellulose acetate" means that a part or all of the raw material cellulose acetate can be molecularly dispersed under any conditions of heating or not heating, and that a clear change in the form of the solid raw material cellulose acetate or its disappearance can be visually observed.
[0079] The alcohol having 3 or less carbon atoms contained in the solvent is not particularly limited. Examples thereof include methanol, ethanol, 1-propanol, and 2-propanol. Among these, methanol and ethanol are preferred, and methanol is more preferred.
[0080] The content of the alcohol having 3 or less carbon atoms in the solvent is preferably 70% by weight or more, more preferably 80% by weight or more, and may be 100% by weight or less.
[0081] The solvent may contain, in addition to an alcohol having 3 or less carbon atoms, acetate, acetic acid, acetone, and the like as optional components. Among these, acetate is preferred, and among acetates, ethyl acetate and methyl acetate are more preferred. This is because the solubility of the starting material (raw material cellulose acetate) and / or the reaction intermediate in the reaction bath can be improved, and cellulose acetate having excellent water solubility and biodegradability can be obtained.
[0082] The content of the optional component other than the alcohol having a carbon number of 3 or less in the solvent is preferably 30% by weight or less, more preferably 20% by weight or less. In particular, when acetate is contained as an optional component, the content of acetate in the solvent is preferably 10% by weight or more and 5% by weight or less.
[0083] The amount of the solvent containing an alcohol having 3 or less carbon atoms used is, for example, 0.5 to 50 parts by weight, preferably 1 to 20 parts by weight, and more preferably 3 to 10 parts by weight, relative to 1 part by weight of the raw material cellulose acetate.
[0084] As the catalyst, an acid catalyst commonly used as a deacetylation catalyst can be used. Examples of the acid catalyst include inorganic acids such as sulfuric acid, hydrochloric acid, and phosphoric acid; and organic acids such as trifluoroacetic acid and formic acid. These acid catalysts can be used alone or in combination of two or more.
[0085] The acid dissociation constant pKa of the acid catalyst in water at 25° C. is preferably 0 or less, more preferably -0.5 or less, and further preferably -1.0 or less. The acid dissociation constant pKa may be -6.0 or more.
[0086] As the acid catalyst, sulfuric acid is preferred. In addition, as sulfuric acid, a sulfuric acid aqueous solution having a sulfuric acid concentration of 98% by weight as concentrated sulfuric acid can be used. The catalyst can be mixed in advance with a solvent containing an alcohol having a carbon number of 3 or less and used for the solvolysis of the raw material cellulose acetate.
[0087] The amount of the acid catalyst used is preferably, for example, 0.005 to 1 part by weight, more preferably 0.01 to 0.5 part by weight, and still more preferably 0.02 to 0.3 part by weight, relative to 1 part by weight of the raw material cellulose acetate. When the amount of the catalyst is too small, the solvolysis time is too long. Although there is an advantage of easy control of the reaction end point, it is not economically preferable. On the other hand, when the amount of the catalyst is too large, the degree of variation of the depolymerization rate relative to the solvolysis temperature is large, and the control of the reaction end point becomes difficult, making it difficult to obtain cellulose acetate having a total degree of substitution of the present disclosure. In addition, it is easy to obtain an uneven cellulose acetate having a deviation in the degree of acetyl substitution.
[0088] The water content in the solvolysis reaction system is as small as possible, and is preferably 2 parts by weight or less, more preferably 1 part by weight or less, and further preferably 0.5 parts by weight or less, relative to 1 part by weight of the raw material cellulose acetate. In addition, there is no lower limit to the water content in the solvolysis reaction system as long as the solvolysis of the raw material cellulose acetate starts and proceeds, and for example, it may be 0.01 parts by weight or more relative to 1 part by weight of the raw material cellulose acetate.
[0089] When the raw material cellulose acetate is subjected to solvolysis, the water originally contained in the raw material cellulose acetate may or may not be removed in advance. The water content of the raw material cellulose acetate may be, for example, 5% by weight or less, 4% by weight or less, or 3% by weight or less, or may be 1% by weight or more.
[0090] The water content contained in the raw material cellulose acetate can be measured by the following method. It can be measured using a Kett moisture meter (METTLER TOLEDO HB43). About 2.0 g of a sample containing water can be placed in the aluminum tray of the Kett moisture meter and heated at 120°C until the weight does not change. The water content (weight %) in the sample can be calculated from the weight change before and after heating.
[0091] In the step of deacetylation by solvolysis of the raw material cellulose acetate, water may be added to the system in addition to the water originally contained in the raw material cellulose acetate. The entire amount may be present in the system at the start of the reaction, or a portion of the water to be used may be present in the system at the start of the reaction, and the remaining water may be added to the system once or several times.
[0092] The content of water in the solvolysis reaction system is preferably 20 parts by weight or less, more preferably 10 parts by weight or less, and even more preferably 5 parts by weight or less, relative to 1 part by weight of the solvent.
[0093] The temperature in the solvolysis reaction system is adjusted to a temperature higher than the boiling point of an alcohol having 3 or less carbon atoms. For example, when methanol is used, the temperature is 65° C. or higher, when ethanol is used, the temperature is 78° C. or higher, when 1-propanol is used, the temperature is 97° C. or higher, and when 2-propanol is used, the temperature is 82° C. or higher. The raw material cellulose acetate is fully dissolved in the solvent, and the solvolysis reaction can be uniformly performed.
[0094] The temperature in the solvolysis reaction system is not limited as long as it is at least the boiling point of the alcohol having 3 or less carbon atoms, but is preferably 105° C. or less, more preferably 100° C. or less, and even more preferably 95° C. or less. When the temperature exceeds 105° C., the degree of polymerization of the obtained cellulose acetate decreases, and the yield decreases significantly.
[0095] The gauge pressure in the solvolysis reaction system is preferably 0.2 MPaG or more and 1 MPaG or less. It is preferably 0.2 MPaG or more and 0.7 MPaG or less, and more preferably 0.2 MPaG or more and 0.5 MPaG or less. When it is 0.2 MPaG or more, the raw material cellulose acetate can be sufficiently dissolved in the solvent, and the solvolysis reaction can be particularly uniformly performed. When it exceeds 1 MPaG, the polymerization degree of the obtained cellulose acetate decreases, and the yield decreases significantly.
[0096] The time of the solvolysis reaction may be from 20 minutes to 300 minutes, from 30 minutes to 240 minutes, from 60 minutes to 200 minutes, or from 60 minutes to 150 minutes. Within this range, the total degree of acetyl substitution can be easily adjusted to 0.4 to 0.9 or less.
[0097] Here, the so-called solvolysis reaction time refers to the time from when the temperature in the solvolysis reaction system is reached to when the temperature is maintained.
[0098] In the conventional deacetylation of raw material cellulose acetate, raw material cellulose acetate is dissolved in a mixed solvent of acetic acid and water, and the raw material cellulose acetate is hydrolyzed using a sulfuric acid catalyst. At this time, the acetyl group is removed substantially equally at the 2nd, 3rd, and 6th positions of the glucose ring of cellulose acetate. On the other hand, in the method for producing cellulose acetate of the present disclosure, the acetyl group at the 6th position is preferentially removed, and cellulose acetate having a low degree of acetyl substitution at the 6th position relative to the degree of acetyl substitution at the 2nd and 3rd positions of the glucose ring is obtained.
[0099] In the conventional deacetylation of raw material cellulose acetate, acetic acid is used as a reaction solvent. During the deacetylation process, acetic acid is preferentially reacetylated at the 6-position, and the reaction proceeds simultaneously. Therefore, apparently, the acetyl group is removed at the 2-position, 3-position, and 6-position of the glucose ring of cellulose acetate in substantially the same manner. If the reacetylation at the 6-position is suppressed, cellulose acetate with a low degree of substitution at the 6-position can be obtained. In this case, a solvent is required to replace acetic acid. The inventors of the present application have conducted intensive studies and found that a solvent containing an alcohol having a carbon number of 3 or less is suitable as a reaction solvent for this purpose when the solvent is at a boiling point or above. When the solvent containing an alcohol having a carbon number of 3 or less is at a boiling point or above, the cellulose acetate having a medium to high degree of substitution of the starting material is dissolved or highly swollen.
[0100] Solvolysis of the raw material cellulose acetate can be completed by adding a neutralizing agent. Examples of the neutralizing agent include salts of weak acids, such as acetates such as sodium acetate and magnesium acetate, and carbonates such as sodium carbonate and magnesium carbonate. The neutralizing agent can be added together with a solvent containing an alcohol having 3 or less carbon atoms.
[0101] The amount of the neutralizing agent used may be 1.0 to 5.0 equivalents, preferably 1.1 to 3.0 equivalents, and more preferably 1.2 to 2.0 equivalents relative to 1 equivalent of the acid catalyst. When the amount of the neutralizing agent is too small, the acid catalyst may remain in the low-substituted cellulose acetate, thereby causing decomposition of the low-substituted cellulose acetate. On the other hand, when the amount of the neutralizing agent is too large, a large amount of solvents are used to wash the neutralizing agent, which is not economically preferable.
[0102] [Precipitation process]
[0103] In the precipitation step in the method for producing cellulose acetate of the present disclosure, cellulose acetate produced by deacetylation of the above-mentioned raw material cellulose acetate is precipitated.
[0104] As a precipitation method, for example, the following method can be mentioned: after the solvolysis reaction of the raw material cellulose acetate is completed, the temperature of the reaction system is cooled to room temperature to precipitate cellulose acetate with a low degree of substitution. In this way, the precipitation method using cooling does not require the addition of a precipitation solvent, which is economically preferred. However, in some cases, the addition of a precipitation solvent can promote the precipitation of cellulose acetate with a low degree of substitution, thereby improving the yield, so a precipitation solvent may be added.
[0105] As the precipitation solvent, there can be mentioned: the above-mentioned solvent containing alcohols having a carbon number of 3 or less; ketones such as acetone and methyl ethyl ketone; esters such as ethyl acetate and methyl acetate; nitrogen-containing compounds such as acetonitrile; ethers such as tetrahydrofuran; and mixed solvents thereof; etc. These precipitation solvents can be used alone or as a mixed solvent containing two or more solvents. Among these, if the same solvent as the reaction solvent is used as the precipitation solvent, it is sometimes easy to recycle and reuse the waste solvent, so the above-mentioned solvent containing alcohols having a carbon number of 3 or less is preferred.
[0106] The precipitation solvent preferably contains the following basic substance. This is to enable neutralization and precipitation to be performed simultaneously.
[0107] [Optional process]
[0108] (Cleaning process, neutralization process)
[0109] The precipitated cellulose acetate is preferably washed with an organic solvent (poor solvent) such as an alcohol such as methanol and a ketone such as acetone. In addition, it is also preferable to wash and neutralize with an organic solvent containing a salt of a weak acid or an alkaline substance (for example, an alcohol such as methanol, a ketone such as acetone, etc.). By washing and neutralizing, impurities such as a catalyst (sulfuric acid, etc.) used in the solvolysis step can be removed efficiently.
[0110] Examples of the weak acid salt include hydrates of acetates such as sodium acetate and magnesium acetate, and hydrates of carbonates such as sodium carbonate and magnesium carbonate. Examples of the alkaline substance include alkali metal compounds such as alkali metal hydroxides such as potassium hydroxide.
[0111] (Purification process)
[0112] By further purifying the precipitated cellulose acetate, cellulose acetate with excellent water solubility can be obtained. In particular, since there is a tendency that the higher the total degree of substitution of acetyl groups in the raw material cellulose acetate, the lower the water solubility of the obtained cellulose acetate, purification is preferably performed. Purification can be performed, for example, by precipitation fractionation (fractional precipitation) and / or dissolution fractionation (fractional dissolution).
[0113] Dissolution fractionation can be performed, for example, by dissolving the precipitated cellulose acetate (solid matter) in water or a mixed solvent of water and a hydrophilic organic solvent (e.g., acetone) to prepare an aqueous solution, and removing the residue (in other words, the insoluble component). Centrifugal separation can be used as a method for removing the residue.
[0114] The dissolution of cellulose acetate may be carried out by stirring at an appropriate temperature (e.g., 20 to 80° C., preferably 25 to 60° C.) The concentration (mixing ratio) of cellulose acetate in the aqueous solution may be adjusted to an appropriate concentration (e.g., 2 to 10% by weight, preferably 3 to 8% by weight).
[0115] When a mixed solvent of water and a hydrophilic organic solvent is used, the concentration of the organic solvent in the mixed solvent may be, for example, 5 to 50% by weight, and preferably 10 to 40% by weight.
[0116] After removing the residue, the dissolved cellulose acetate is precipitated. Examples of the precipitation method include reprecipitation and spray drying. Examples of the precipitation solvent used in the reprecipitation include: the above-mentioned solvents containing alcohols having 3 or less carbon atoms; ketones such as acetone and methyl ethyl ketone; esters such as ethyl acetate and methyl acetate; nitrogen-containing compounds such as acetonitrile; ethers such as tetrahydrofuran; and mixed solvents thereof; etc. These precipitation solvents may be used alone or as a mixed solvent containing two or more solvents.
[0117] (Add stabilizer)
[0118] After precipitating cellulose acetate, a stabilizer may be added to the precipitated cellulose acetate. This is to improve the thermal stability of cellulose acetate. As the stabilizer, an alkali metal compound and / or an alkaline earth metal compound, particularly a potassium compound such as potassium hydroxide, is preferred.
[0119] The amount of the stabilizer to be added is preferably, for example, a reaction mixture containing cellulose acetate and an aqueous potassium hydroxide solution adjusted to 0.2 to 1.0 wt % are added at a volume ratio of 100:1 to 10.
[0120] The stabilizer may be added at the same time as the free metal component, sulfuric acid component, etc. are removed by washing (using a poor solvent such as the precipitation solvent of the precipitate).
[0121] It is preferred that the cellulose acetate is dried after the step of precipitating the deacetylated cellulose acetate or after the optional step when the optional step is included. When the cellulose acetate is dried, the drying method is not particularly limited, and a conventionally known method can be used. For example, drying by air blowing such as hot air drying, drying under reduced pressure, and drying by vacuum drying can be mentioned. The temperature and pressure may be appropriately adjusted.
[0122] After drying the cellulose acetate, the cellulose acetate may be pulverized. The pulverization may be performed using a conventional pulverizer, such as a sample mill, a hammer mill, a turbo mill, an atomizer, a cutter mill, a bead mill, a ball mill, a roller mill, a jet mill, a pin mill, etc. In addition, the pulverization may be performed by freeze pulverization, dry pulverization at room temperature, or wet pulverization.
[0123] Example
[0124] Hereinafter, the present invention will be specifically described using examples, but the technical scope of the present invention is not limited to these examples.
[0125] <Preparation and Properties of Cellulose Acetate>
[0126] Regarding the cellulose acetates of Examples and Comparative Examples, the physical properties described in Table 1 were measured as follows.
[0127] (Reaction product yield)
[0128] The reaction product yield (yield of cellulose acetate before the purification step) (weight %) was calculated as follows.
[0129] Reaction product yield (weight %) = actual yield of solvolysis reaction product (when the purification step is included, the cellulose acetate before the purification step) / theoretical yield of solvolysis reaction product (when the purification step is included, the cellulose acetate before the purification step)
[0130] (Purified product yield)
[0131] The yield (weight %) of the purified product was calculated as follows.
[0132] Purified product yield (yield of cellulose acetate after the purification step) (weight %) = actual yield of purified product (when the purification step is included, the cellulose acetate after the purification step) / actual yield of solvolysis reaction product (when the purification step is included, the cellulose acetate before the purification step)
[0133] (Total degree of acetyl substitution, degrees of acetyl substitution at the 2nd, 3rd and 6th positions (DS2, DS3, and DS6), ratio of the degree of acetyl substitution at the 6th position to the total degree of acetyl substitution)
[0134] According to the literature of Tezuka et al. (Carbohydrate Research, 273, 83-91 (1995)), the sample was propionylated with propionic anhydride in pyridine solvent and then measured in chloroform solvent. 13 In the C-NMR spectrum, the intensities of the three signals of the carbonyl carbon of the acetyl group appearing around 169.1 to 170.2 ppm were integrated, and the intensities of the three signals of the carbonyl carbon of the propionyl group appearing around 172.7 to 173.6 ppm were integrated.
[0135] 13 In the C-NMR spectrum, the three signals of the carbonyl carbon of the acetyl group appearing around 169.1 to 170.2 ppm are respectively assigned to the 2nd, 3rd, and 6th positions from the high magnetic field side. The intensity in the range of ±0.2 ppm relative to the maximum of each signal is integrated and defined as the integrated intensity of the carbonyl carbon signal of each acetyl group. DS is calculated according to the following formula i (i is 2, 3 or 6).
[0136] DS i =DS×(integral intensity of carbonyl carbon signal of acetyl group at position i) / (sum of integral intensity of carbonyl carbon signal of acetyl groups at positions 2, 3 and 6)
[0137] The NMR measurement conditions are as follows.
[0138] Determination solvent: CDCl3 (approximately 3 ml)
[0139] Measurement temperature: 40℃
[0140] Sample amount: 160~180mg( )
[0141] Observed nucleus: 13C (1H fully decoupled)
[0142] Number of data points: 32768
[0143] Pulse angle and time: 45°, 9 microseconds
[0144] Data acquisition time: 0.9667 seconds
[0145] Waiting time: 2.0333 seconds
[0146] Cumulative times: 18,000 times
[0147] The total degree of substitution (DS) of acetyl groups was determined according to the following formula, where the integrated intensity of the carbonyl carbon signal of the acetyl group was X and the integrated intensity of the carbonyl carbon signal of the propionyl group was Y.
[0148] Total degree of acetyl substitution (DS) = 3 × [X / (X+Y)]
[0149] The ratio (%) of the degree of substitution of acetyl groups at the 6-position to the total degree of substitution of acetyl groups was determined according to the following formula.
[0150] The ratio of acetyl substitution degree at position 6 (%) = acetyl substitution degree at position 6 (DS6) / total acetyl substitution degree (DS) × 100
[0151] (Degree of Polymerization (Viscosity Average Degree of Polymerization))
[0152] The degree of polymerization of cellulose acetate was evaluated as a viscosity average degree of polymerization based on the intrinsic viscosity number ([η], unit: g / ml).
[0153] Specifically, first, regarding the intrinsic viscosity of cellulose acetate, according to JIS-K-7367-1 and ISO1628-1, an Ubbelohde viscometer with a size number of 1C is used as a viscometer, dimethyl sulfoxide (DMSO) is used as a solvent, and the logarithmic relative viscosity at 25° C. is divided by the concentration to determine the value.
[0154] Next, according to the literature of Kamide et al., the molecular weight (viscosity average molecular weight) of cellulose acetate was calculated from the following formula.
[0155] Viscosity average molecular weight = (intrinsic viscosity number [η] / 0.171) (1 / 0.61)
[0156] The degree of polymerization (viscosity average degree of polymerization) of cellulose acetate was determined from the following formula.
[0157] Degree of polymerization (viscosity average degree of polymerization) = viscosity average molecular weight / (162.14 + 42.037 × DS)
[0158] (Transmittance (Transmittance of 4 wt% aqueous solution))
[0159] 0.4 g of cellulose acetate was dispersed in 10 ml of water, stirred for 2 hours with a magnetic stirrer, left to stand overnight, and stirred again for 2 hours. The transmittance (%) at 660 nm of a 4% aqueous solution of cellulose acetate obtained as described below was measured using a spectrophotometer (manufactured by Shimadzu Corporation, UV-visible spectrophotometer UV-1800, cell material: polystyrene, cell length: 10 mm).
[0160] (Example A-1)
[0161] Deacetylation process:
[0162] 70 parts by weight of cellulose diacetate (manufactured by Daicel Co., Ltd., trade name "L-50", water content 3% by weight, total acetyl substitution degree 2.43, 2-position acetyl substitution degree 0.86, 3-position acetyl substitution degree 0.82, 6-position acetyl substitution degree 0.75) as a raw material of cellulose acetate was added to 554 parts by weight of methanol as a solvent at room temperature, and further 3.5 parts by weight of sulfuric acid as a catalyst was added. The mixture was heated to 90°C over a heating time of 50 minutes while being stirred, and the temperature was controlled (maintained) at 90°C for 100 minutes.
[0163] Sedimentation process:
[0164] The reaction mixture was cooled to room temperature, and a mixture of 14.6 parts by weight of sodium acetate trihydrate and 55 parts by weight of methanol was added to neutralize the sulfuric acid. The white solid suspended in the reaction mixture was filtered by suction. The filtered white solid was suspended in 277 parts by weight of methanol and stirred at room temperature for 1 hour. The white solid in the methanol was filtered by suction.
[0165] The filtered white solid was resuspended in 277 parts by weight of methanol and stirred at room temperature for 1 hour. The white solid in the methanol was filtered by suction. The white solid washed with methanol was dried under reduced pressure at 60°C until a constant weight was obtained, thereby obtaining 42 parts by weight of low-substituted cellulose acetate. The various physical properties of the obtained low-substituted cellulose acetate were measured, and the results are shown in Table 1.
[0166] (Example A-2)
[0167] Deacetylation process and precipitation process:
[0168] By the same method as in Example A-1, 42 parts by weight of low-substituted cellulose acetate was obtained.
[0169] Purification process:
[0170] Furthermore, the low-substituted cellulose acetate was added to 1,440 parts by weight of water, stirred at room temperature for 8 hours, and left to stand overnight. The suspension was centrifuged at 12,600G for 30 minutes to obtain a supernatant of the suspension. The supernatant was added dropwise to 10,000 parts by weight of acetone under stirring to obtain a white precipitate. The white precipitate was filtered by suction and dried under reduced pressure at 60°C to a constant weight, thereby obtaining 54 parts by weight of low-substituted cellulose acetate. The various physical properties of the obtained low-substituted cellulose acetate were measured, and the results are shown in Table 1.
[0171] (Example A-3)
[0172] Deacetylation process and precipitation process:
[0173] 47 parts by weight of low-substituted cellulose acetate was obtained by the same method as in Example A-1 except that cellulose acetate (trade name "CA-320S" manufactured by Eastman Chemical Company, moisture content 3% by weight, total acetyl substitution degree 1.80, acetyl substitution degree at position 2 0.61, acetyl substitution degree at position 3 0.56, acetyl substitution degree at position 6 0.63) was used instead of cellulose diacetate (manufactured by Daicel Co., Ltd., trade name "L-50", moisture content 3% by weight), and the temperature control time at 90° C. was changed to 80 minutes. The physical properties of the obtained low-substituted cellulose acetate were measured, and the results are shown in Table 1.
[0174] (Example A-4)
[0175] 41 parts by weight of low-substituted cellulose acetate was obtained by the same method as in Example A-1 except that cellulose acetate (manufactured by Daicel Corporation, trade name "L-50", water content 3% by weight) was replaced with cellulose acetate (manufactured by Daicel Corporation, trade name "LM-80", water content 3% by weight, total acetyl substitution degree 2.14, acetyl substitution degree at position 2 0.75, acetyl substitution degree at position 3 0.75, acetyl substitution degree at position 6 0.64) and the temperature control (maintaining) time at 90°C was changed to 125 minutes. The physical properties of the obtained low-substituted cellulose acetate were measured, and the results are shown in Table 1.
[0176] (Example A-5)
[0177] Cellulose diacetate (manufactured by Daicel Corporation, trade name "L-50", water content 3 wt%) was used and the temperature control (maintenance) time at 90°C was changed to 65 minutes. 45 parts by weight of low-substituted cellulose acetate was obtained by the same method as in Example A-1. The various physical properties of the obtained low-substituted cellulose acetate were measured, and the results are shown in Table 1.
[0178] (Example A-6)
[0179] 38 parts by weight of low-substituted cellulose acetate was obtained by the same method as in Example A-1 except that cellulose diacetate (manufactured by Daicel Corporation, trade name "L-50", water content 3% by weight) was used and the temperature control (maintenance) time at 90° C. was set to 130 minutes. The various physical properties of the obtained low-substituted cellulose acetate were measured, and the results are shown in Table 1.
[0180] (Comparative Example A-1)
[0181] Deacetylation process:
[0182] 100 parts by weight of cellulose diacetate (manufactured by Daicel Co., Ltd., trade name "L-50", water content 3% by weight, total acetyl substitution degree 2.43, acetyl substitution degree at position 2 0.86, acetyl substitution degree at position 3 0.82, acetyl substitution degree at position 6 0.75) as a raw material of cellulose acetate was added to a mixture (mixed solvent) of 358 parts by weight of acetic acid and 95 parts by weight of water as a solvent, and stirred at 70°C for 5 hours, and then allowed to stand at room temperature (about 25°C) overnight. The mixture was brought to 70°C, and 178 parts by weight of water was added to obtain a cellulose diacetate solution.
[0183] The cellulose diacetate solution was temperature controlled at 50°C, and a mixture of 12.6 parts by weight of 98% sulfuric acid (catalyst) and 57 parts by weight of acetic acid (solvent) was added. The reaction mixture was temperature controlled at 50°C while stirring, and 137 parts by weight of water was added over 30 minutes 4 hours after the addition of sulfuric acid, and 111 parts by weight of water was added over 30 minutes 8 hours after the addition of sulfuric acid. The reaction mixture was temperature controlled at 50°C while stirring, and 23 hours and 40 minutes after the addition of sulfuric acid (1,420 minutes later), a mixture of 72 parts by weight of sodium acetate trihydrate and 109 g of water was added to stop the reaction.
[0184] Sedimentation process:
[0185] The reaction mixture was added dropwise to 4,700 parts by weight of methanol under stirring to obtain a white precipitate. The following operation was repeated 5 times: the white precipitate was filtered, dispersed in 1,100 parts by weight of methanol, and filtered again. The filtered white precipitate was dried under reduced pressure at 60°C to a constant weight, thereby obtaining 62 parts by weight of low-substituted cellulose acetate. The various physical properties of the obtained low-substituted cellulose acetate were measured, and the results are shown in Table 1.
[0186] (Comparative Example A-2)
[0187] Low-substituted cellulose acetate was obtained by the method according to Example 17 of Japanese Patent No. 6378712. The details are as follows.
[0188] Deacetylation process:
[0189] A mixture of 510 parts by weight of acetic acid and 95 parts by weight of water was added to 100 parts by weight of cellulose diacetate (manufactured by Daicel Co., Ltd., trade name "L-50", water content 3% by weight, total acetyl substitution degree 2.43, acetyl substitution degree at position 2 0.86, acetyl substitution degree at position 3 0.82, acetyl substitution degree at position 6 0.75) and stirred at 70°C for 3 hours to obtain a cellulose diacetate solution. While stirring the cellulose diacetate solution, the temperature was controlled at 70°C, and 13 parts by weight of 98% sulfuric acid was added. While continuing to stir the reaction mixture, the temperature was controlled at 70°C, and 3 hours after the addition of sulfuric acid, 67 parts by weight of water was added over 5 minutes, and 8 hours after the addition of sulfuric acid, 133 parts by weight of water was added over 10 minutes. While continuing to stir the reaction mixture, the temperature was controlled at 70°C, and 10 hours after the addition of sulfuric acid (600 minutes later), the reaction mixture was cooled to 25°C, and the reaction was substantially stopped.
[0190] Sedimentation process:
[0191] The reaction mixture was added dropwise to 1,500 parts by weight of acetone under stirring to obtain a white precipitate. The following operation was repeated three times: the white precipitate was filtered, dispersed in 800 parts by weight of acetone, and filtered again. The following operation was repeated twice: the filtered white precipitate was dispersed in 800 parts by weight of methanol containing 0.004% by weight of potassium acetate, and filtered again. The filtered white precipitate was dried under reduced pressure at 60°C to a constant weight. 960 parts by weight of a 20% by weight acetone aqueous solution was added to 64 parts by weight of the dried product, and after stirring at 40°C for 8 hours, the concentrated phase was removed by centrifugation, and 1 part by weight of acetone was added to the dilute phase to obtain a white precipitate. The white precipitate was filtered, dispersed in 3,000 parts by weight of acetone, and filtered again. The filtered white precipitate was dried under reduced pressure at 60°C to a constant weight, thereby obtaining 57 parts by weight of low-substituted cellulose acetate. The physical properties of the obtained low-substituted cellulose acetate were measured. The results are shown in Table 1.
[0192] (Comparative Example A-3)
[0193] Low-substituted cellulose acetate was obtained according to the conditions of Experiment No. 6 of Edgar et al., Macromolecules, 24, 3060 (1991).
[0194] Specifically, 60 parts by weight of cellulose diacetate (manufactured by Daicel Co., Ltd., trade name "L-50", used after being dried under reduced pressure at 60°C to a constant weight) were suspended in 237 parts by weight of methanol, 0.2 parts by weight of molybdenum hexacarbonyl (Mo(CO)6) was added, and the internal pressure was adjusted to 200 psi in a closed reactor using nitrogen gas, and the temperature was controlled at 140°C for 7 hours (420 minutes). The reaction mixture was cooled to room temperature, and the solid in the reaction mixture was filtered by suction filtration. The filtered solid was dried under reduced pressure at 60°C to a constant weight, thereby obtaining 34 parts by weight of low-substituted cellulose acetate. The various physical properties of the obtained low-substituted cellulose acetate were measured, and the results are shown in Table 1.
[0195] (Comparative Example A-4)
[0196] Low-substituted cellulose acetate was obtained according to the conditions of Experiment No. 7 of Edgar et al., Macromolecules, 24, 3060 (1991).
[0197] Specifically, 60 parts by weight of cellulose diacetate (manufactured by Daicel Co., Ltd., trade name "L-50", used after being dried under reduced pressure at 60°C to a constant weight) was suspended in 237 parts by weight of methanol, 0.2 parts by weight of molybdenum (VI) oxide (MoO3) was added, and the internal pressure was adjusted to 1,000 psi in a closed reactor using nitrogen gas, and the temperature was controlled at 155°C for 3 hours (180 minutes). The reaction mixture was cooled to room temperature, and the solid in the reaction mixture was filtered by suction filtration. The filtered solid was dried under reduced pressure at 60°C to a constant weight, thereby obtaining 33 parts by weight of low-substituted cellulose acetate. The various physical properties of the obtained low-substituted cellulose acetate were measured, and the results are shown in Table 1.
[0198] (Comparative Example A-5)
[0199] 43 parts by weight of low-substituted cellulose acetate was obtained by the same method as in Example A-1 except that cellulose diacetate (manufactured by Daicel Corporation, trade name "L-50", water content 3% by weight) was used and the temperature control (maintenance) time at 90° C. was changed to 50 minutes. The physical properties of the obtained low-substituted cellulose acetate were measured, and the results are shown in Table 1.
[0200] (Comparative Example A-6)
[0201] 34 parts by weight of low-substituted cellulose acetate was obtained by the same method as in Example A-1 except that cellulose diacetate (manufactured by Daicel Corporation, trade name "L-50", water content 3% by weight) was used and the temperature control (maintenance) time at 90°C was set to 160 minutes. The various physical properties of the obtained low-substituted cellulose acetate were measured, and the results are shown in Table 1.
[0202] [Table 1]
[0203]
[0204] In the cellulose acetate of Comparative Example A-1, the degree of acetyl substitution at the 6-position is 0.24, and the proportion of the acetyl substitution at the 6-position in the total acetyl substitution degree is 36.9%. In the cellulose acetate of Comparative Example A-2, the degree of acetyl substitution at the 6-position is 0.28, and the proportion of the acetyl substitution at the 6-position in the total acetyl substitution degree is 35.9%. The degrees of acetyl substitution at the 6-position of the cellulose acetates of Comparative Examples A-1 and A-2 are higher than the degrees of acetyl substitution at the 2-position and the 3-position.
[0205] The cellulose acetate of Comparative Example A-3 had an acetyl substitution degree at the 6-position of 0.05, and the proportion of the acetyl substitution degree at the 6-position in the total acetyl substitution degree was 10.4%. The cellulose acetate of Comparative Example A-4 had an acetyl substitution degree at the 6-position of 0.06, and the proportion of the acetyl substitution degree at the 6-position in the total acetyl substitution degree was 12.0%. The acetyl substitution degree at the 6-position of the cellulose acetates of Comparative Examples A-3 and A-4 was lower than the acetyl substitution degree at the 2-position and the 3-position. However, the transmittance at 660 nm of a 4 wt % aqueous solution was low, and the water solubility was insufficient.
[0206] The cellulose acetate of Comparative Example A-5 had an acetyl substitution degree at the 6-position of 0.13, and the proportion of the acetyl substitution degree at the 6-position in the total acetyl substitution degree was 13.1%. The cellulose acetate of Comparative Example A-6 had an acetyl substitution degree at the 6-position of 0.03, and the proportion of the acetyl substitution degree at the 6-position in the total acetyl substitution degree was 9.1%. The acetyl substitution degrees at the 6-position of the cellulose acetates of Comparative Examples A-5 and A-6 were lower than the acetyl substitution degrees at the 2-position and the 3-position. However, the transmittance at 660 nm of a 4 wt % aqueous solution was low, and the water solubility was insufficient.
[0207] On the other hand, the cellulose acetates of Examples A-1 to A-6 had a low ratio of acetyl substitution at the 6-position to the total acetyl substitution, being 18% or less, and a light transmittance of 4 wt % aqueous solution at 660 nm being 5% or more, indicating excellent water solubility. In particular, the light transmittance of 4 wt % aqueous solution of the cellulose acetates of Examples A-2 and A-3 at 660 nm being 92% or more, indicating particularly excellent water solubility.
[0208] <Animal experiments (acetyl residue rate, feed intake, weight gain, blood sugar level, cholesterol, neutral fat, epididymal fat)>
[0209] Animal experiments were conducted using nine 7-week-old male Wistar rats (SLC Co., Ltd., Japan) that were housed separately in stainless steel cages at room temperature of 24±1°C, relative humidity of 55±5°C, and a 12-hour light-dark cycle (lights on from 7:00 to 19:00).
[0210] After the rats were moved in, they were acclimated by feeding the purified feed AIN-93G (Reeves et al., Journal of Nutrition, 123, 1939-1951 (1993)) together with tap water for 3 days, and then divided into three groups based on body weight (for eliminating the deviation of the total body weight of each group of rats), and the rats were respectively divided into three groups, namely, Group 1, which freely ingested AIN-93G (sometimes referred to as "control group") together with tap water for 14 days, Group 2, which freely ingested AIN-93G containing 5% by weight of the low-substituted cellulose acetate of Example A-2 (sometimes referred to as "test group") together with tap water for 14 days, and Group 3, which freely ingested AIN-93G containing 5% by weight of the low-substituted cellulose acetate of Comparative Example A-1 (sometimes referred to as "comparative group") together with tap water for 14 days. The number of rats in each group consisted of 3 rats. Respectively, Group 1 corresponds to Reference Example B-1, Group 2 corresponds to Example B-1, and Group 3 corresponds to Comparative Example B-1.
[0211] The rats were divided into three groups, and on the third, seventh, and thirteenth days after the start of feeding on each feed, all feces of one day were collected and analyzed for the residual acetyl group rate. The analysis method is as follows. In addition, the feed intake and body weight gain were measured during the entire feeding period.
[0212] On the 14th day of feeding, the rats were fasted from 7:00 a.m. and dissected from 15:00. The rats were opened under isoflurane anesthesia, and about 2 mL of blood was collected from the abdominal aorta and added to a heparinized test tube (VENOJECT II heparin sodium, 3 mL for blood collection: Terumo Corporation). Then, the rats were bled to perform euthanasia, and the epididymal fat (left and right) was quickly removed. Then, the weight of epididymal fat was measured.
[0213] The collected blood was centrifuged at 2,380G for 10 minutes at room temperature to separate the plasma. For the separated plasma, the blood sugar level was measured using CicaLiquid GLU (Kanto Chemical Co., Ltd.) on the day of blood collection; neutral fat (triglyceride) was measured using CicaLiquid-N TG (Kanto Chemical Co., Ltd.); and cholesterol (also called plasma cholesterol) was measured using CicaLiquid-NCHO (Kanto Chemical Co., Ltd.).
[0214] <Acetyl group residual rate>
[0215] 0.1 g of rat feces was suspended in 10 ml of water, and the acetic acid contained in the rat feces was derivatized to the corresponding 2-nitrophenylhydrazine by the method of Miwa et al. (Journal of Chromatography, 321, 165-174 (1985)). The acetic acid concentration in the rat feces was determined by quantifying the 2-nitrophenylhydrazine of the acetic acid by HPLC analysis.
[0216] In addition, 0.1 g of rat feces was suspended in a 150 mM sodium hydroxide aqueous solution and the temperature was controlled at 70°C for 4 hours. The acetic acid contained in the rat feces treated with sodium hydroxide was derivatized to the corresponding 2-nitrophenylhydrazine using the method of Miwa et al. (Journal of Chromatography, 321, 165-174 (1985)). The acetic acid concentration of the rat feces treated with sodium hydroxide was determined by quantifying the 2-nitrophenylhydrazine of the acetic acid using HPLC analysis.
[0217] The difference between the acetic acid concentration of rat feces treated with sodium hydroxide and the acetic acid concentration of rat feces suspended in water was taken as the acetyl group concentration (number of moles per unit weight) of rat feces. The acetyl group residual rate was calculated by the following formula.
[0218] Residual acetyl rate (mol%) = 100 × (acetyl concentration in rat feces) × A / (B × C / D)
[0219] A: Rat feces volume (weight) from 0 to 24 hours
[0220] B: Feed intake (weight) of rats from -24 hours to 0 hours
[0221] C: Concentration of cellulose acetate in feed (weight %)
[0222] D: Number of moles of acetyl groups per unit weight of cellulose acetate
[0223] =DS / (162.14+42.037×DS)
[0224] DS: total degree of acetyl substitution
[0225] [Table 2]
[0226]
[0227] *P<0.05, significant compared with the control group (Dunnet test)
[0228] **P<0.01, significant compared with the control group (Dunnet test)
[0229] The residual acetyl rates in feces of rats fed with cellulose acetate of Example A-2 (the ratio of acetyl substitution at position 6 to the total acetyl substitution ratio being 18% or less) (Example B-1) on the 3rd, 7th and 13th days of feeding were all lower than those of rats fed with cellulose acetate of Comparative Example A-1 (the ratio of acetyl substitution at position 6 to the total acetyl substitution ratio being more than 18%) (Comparative Example B-1). This indicates that the cellulose acetate of the Examples with a low ratio of acetyl substitution at position 6 is excellent in decomposability and is easily metabolized in the body.
[0230] Compared with Reference Example B-1 (control group), the feed intake of rats in Comparative Example B-1 (comparative group) was significantly lower, but no significant difference was observed in the amount of weight gain. On the other hand, the feed intake and weight gain of rats in Example B-1 (test group) were lower than those in Comparative Example B-1 (comparative group), and a significant difference was observed with respect to Reference Example B-1 (control group).
[0231] The blood sugar level and cholesterol of the rats of Example B-1 (test group) showed no significant difference compared with those of Reference Example B-1 (control group), but showed a tendency to decrease.
[0232] In addition, the neutral fat of the rats of Comparative Example B-1 (comparative group) was not significantly different from that of Reference Example B-1 (control group). On the other hand, the neutral fat of the rats of Example B-1 (test group) was lower than that of Reference Example B-1 (control group), and a significant difference was observed.
[0233] In addition, the epididymal fat of the rats of Comparative Example B-1 (comparative group) and Example B-1 (test group) was lower than that of the rats of Reference Example B-1 (control group), and a significant difference was observed.
[0234] As described above, it is known that the cellulose acetate of the Examples having a low acetyl substitution ratio at the 6-position is excellent in degradability and is easily metabolized in the body, and contributes particularly to appetite suppression (feed intake suppression), weight gain suppression, neutral fat suppression, and fat accumulation suppression (epididymal fat suppression) in rats.
Claims
1. Cellulose acetate having a total degree of acetyl substitution of 0.4 or more and 0.9 or less, The proportion of the acetyl substitution degree at the 6-position in the total acetyl substitution degree is greater than 0% and less than 18%, The viscosity average polymerization degree is 11 or more and 65 or less, and The light transmittance of a 4 wt % aqueous solution at 660 nm is 5% or more.
2. The cellulose acetate according to claim 1, wherein The 4 wt % aqueous solution has a light transmittance of 80% or more at 660 nm.
3. The method for producing cellulose acetate according to claim 1 or 2, comprising the following steps: A step of deacetylation by solvolysis of raw material cellulose acetate having a total degree of acetyl substitution of 1.5 to 3.0; and a step of precipitating cellulose acetate produced by deacetylation of the raw material cellulose acetate, The solvolysis of the raw material cellulose acetate is carried out in the presence of a solvent containing an alcohol having 3 or less carbon atoms and an acid catalyst at a temperature not lower than the boiling point of the alcohol. The acid catalyst is sulfuric acid, the content of the optional components other than the alcohol having 3 or less carbon atoms in the solvent is 30% by weight or less, The solvolysis reaction time is 60 minutes or more and 150 minutes or less.
4. The method for producing cellulose acetate according to claim 3, wherein The acid catalyst has an acid dissociation constant pKa of 0 or less in water at 25°C.
5. The method for producing cellulose acetate according to claim 3 or 4, wherein The alcohol is methanol.
6. The method for producing cellulose acetate according to any one of claims 3 to 5, wherein The solvent comprises acetate.
7. The method for producing cellulose acetate according to any one of claims 3 to 6, comprising the following steps: The process of dissolving the precipitated cellulose acetate in water and removing the residue; and a step of precipitating the dissolved cellulose acetate.
8. The method for producing cellulose acetate according to any one of claims 3 to 7, comprising the following steps: The step of dissolving the precipitated cellulose acetate in water and centrifuging to remove residues; and A step of reprecipitating the dissolved cellulose acetate.
9. Cellulose acetate having a total degree of acetyl substitution of 0.4 or more and 0.9 or less, The proportion of the acetyl substitution degree at the 6-position in the total acetyl substitution degree is greater than 0% and less than 18%, The viscosity average polymerization degree is 11 or more and 65 or less, and The transmittance of a 4 wt% aqueous solution at 660 nm is 5% or more. The cellulose acetate is produced by a production method having the following steps: A step of deacetylation by solvolysis of raw material cellulose acetate having a total degree of acetyl substitution of 1.5 to 3.0; and a step of precipitating cellulose acetate produced by deacetylation of the raw material cellulose acetate, The solvolysis of the raw material cellulose acetate is carried out in the presence of a solvent containing an alcohol having 3 or less carbon atoms and an acid catalyst at a temperature not lower than the boiling point of the alcohol. The acid catalyst is sulfuric acid, the content of the optional components other than the alcohol having 3 or less carbon atoms in the solvent is 30% by weight or less, The solvolysis reaction time is 60 minutes or more and 150 minutes or less.
Citation Information
Patent Citations
Manufacture of optical disc board
JP1988078712A
Printing system
JP1989053851A